Excess stroke incidence in young Aboriginal people in South Australia: Pooled results from two population-based studies. Issue 8 (October 2018) - Balabanski, Anna H; Newbury, Jonathan; Leyden, James M; Arima, Hisatomi; Anderson, Craig S; Castle, Sally; Cranefield, Jennifer; Paterson, Tracey; Thrift, Amanda G; Katzenellenbogen, Judith; Brown, Alex; Kleinig, Timothy J
Background: Retrospective data indicate increased stroke incidence in Aboriginal/Torres Strait Islander (Indigenous) Australians, possibly with poorer outcomes. We present the first prospective population-based stroke incidence study in Indigenous Australians. Methods: We pooled data from ASCEND and SEARCH, two prospective "ideal" South Australian stroke incidence studies, ASCEND conducted in urban Northwestern Adelaide (2009–2010) and SEARCH in five South Australian rural centers (2009–2011). We calculated age-standardized incidence for Aboriginal and non-Aboriginal people. Results: The study population comprised 261, 403 inhabitants. Among 432 first-ever strokes, 13 were in Aboriginal people (median age 51 vs. 78 years for non-Aboriginal people, p < 0.001). Age-standardized stroke incidence per 100, 000 in Aboriginal patients (116, 95% CI: 95–137) was nearly two-fold that of non-Aboriginal patients (67, 95% CI: 51–84). Age-stratified excess incidence in Aboriginal people was restricted to those aged < 55 years (incidence rate ratio (IRR) 3.5, 95% CI: 2–7), particularly for intracerebral hemorrhage (IRR: 16, 95% CI: 4–61). Conclusion: The excess stroke incidence in Aboriginal South Australians appears substantial, especially in those aged <55 years. Further work is required to delineate and address disparities.